A RE-READING OF THE BRAZILIAN NOVEL MACUNAÍMA - Da Conceição, David (2017)
The present article aims at making a re-reading of the Brazilian novel Macunaíma based on a dialogue between the Social Sciences (in particular Anthropology) and Literature, seeking a better understanding of this object and the concept of culture. In an attempt to address such proposal, this article analyses the Modernism and its relation with modernity, through a discussion anchored in some works carried out by authors of Philosophy (such as Cornelius Castoriadis) and others studies offered by the sociological thought (Gilberto Velho, among others). Summing up, the objective is to highlight the construction of Brazilian cultural identity, having as a reference the contributions of Macunaíma.